Comperative Study between Caudal & Subarachnoid Block in Children for Sub-Umbilical Surgery (Bangladesh Journal of Neurosurgery, 2022)
Background: Caudal block has slower onset and is frequently practiced as a supplemental but Sabarachnoid block has rapid onset and with good haemodynamic stabilityin children but there remains some hesitation in its use.affectivenes of subarachnoid blockObjectives: To compare the time of onset of sensory block, its haemodynamic stability andaffectivenes of subarachnoid block in children for subumbilical surgery.Methods: In this study 60 patients who fulfilled the eligibility criteria were chosen and the procedure was explained to the patient’s attendant. After obtaining written and informed consent, patients were randomized into two equal groups of 30 each. Group-S was given spinalanaesthesia with 0.5% hyperbaric bupivacaine in a dose of 0.4mg/kg over 10 secends. Group-C was given caudal block with 0.25%plain bupivacaine 2mg/kg in volume of 1ml/kg. Patients were observed for time and duration of onset&level of sensory block, need ofadjuvants, hemodynamics condition and per-operative complications if any.Results: The study showed rapid onset of sensory block in Group-S without any supliment and with a good haemodynamics stability. Sensory level block achieved in more than 90% cases of group-S wasT6 while in group-C it was T8 level in 64% cases. No major per-operative complications occurred in either group.Conclusion: The anaesthesiologists who care for infants and children during their practice should have option for spinal anaesthesia as an alternative to general anaesthesia forshort surgical procedures below umbilicus requiring immediate relaxation.Bang. J Neurosurgery 2022; 11(2): 101-106